2020
DOI: 10.1016/j.plantsci.2020.110586
|View full text |Cite
|
Sign up to set email alerts
|

Impedance flow cytometry allows the early prediction of embryo yields in wheat (Triticum aestivum L.) microspore cultures

Abstract: Haplomethods are key biotechnological tools that make it possible to rapidly produce perfectly homozygous lines, speeding up plant breeding programs. Under specific stress conditions, microspores are reprogrammed toward sporophytic pathways, leading to embryo formation.Various endogenous and exogenous factors affect embryo yield in androgenesis, so the improvement of androgenesis efficiency requires the development of early, reliable and robust reactivity markers. During the last decade, numerous cytological, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…As a closing remark, IFC turned out to be strikingly useful for the label-free characterization of hazelnut pollen in a high throughput, allowing the fast identification of hazelnut cultivars with high male sterility. Moreover, its versatility holds great promise for numerous research applications in hazelnut pollen biology and pollination ecology and has the potential to simplify haploid plant production for hazelnut breeding purposes ( Gniech Karasawa et al, 2016 ), as demonstrated by recent studies on wheat ( Canonge et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a closing remark, IFC turned out to be strikingly useful for the label-free characterization of hazelnut pollen in a high throughput, allowing the fast identification of hazelnut cultivars with high male sterility. Moreover, its versatility holds great promise for numerous research applications in hazelnut pollen biology and pollination ecology and has the potential to simplify haploid plant production for hazelnut breeding purposes ( Gniech Karasawa et al, 2016 ), as demonstrated by recent studies on wheat ( Canonge et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, label-free impedance flow cytometry (IFC) was demonstrated as a useful alternative to the above-mentioned techniques for the analysis of microspore development and characterization of pollen viability in different plant species ( Heidmann et al, 2016 ; Heidmann and Di Berardino, 2017 ; Canonge et al, 2020 ; Impe et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the most relevant factors affecting microspore embryogenesis, is the microspore and pollen stage of development. It is widely accepted how vacuolate microspores and young bi-cellular pollen grains are more sensitive to the androgenic induction ( Maheshwari et al, 1980 ; Dunwell, 2010 ; Dwivedi et al, 2015 ; Canonge et al, 2020 ). On the other hand, it has been demonstrated in different species how microspore and pollen stage of development can be correlated with some features of the flower, as is the case of bud length, pedicel length, anther length and petal to anther ratio in Brassica napus L. ( Pechan and Keller, 1988 ), bud length and perianth morphological markers in Solanum lycopersicum L. ( Brukhin et al, 2003 ), pigmentation degree of anthers ( Kim et al, 2004 ) and calyx-corolla ratio ( Bárány et al, 2005 ) in Capsicum annuum L., or more recently, flower bud size in Stevia rebaudiana Bertoni ( Uskutoǧlu et al, 2019 ), and bud length, anther color, and filament length in Opuntia ficus-indica L. Mill ( Bouamama-Gzara et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This technology has shown its potential for single-cell analysis in samples containing a wide range of cell types. It has been used to characterize the electrical properties of Red Blood Cells (RBCs) [6], to analyze plant spores [7], to identify the differentiation state of Mesenchymal Stem Cells (MSCs) [8], to characterize and classify tumor cells [9], to study the effect of chemotherapy treatment on the cell membrane of HeLa cells [10], to monitor the viability of yeast cells [11] and to analyze pollen samples [12]. Due to their small size, it can be difficult to achieve sufficient signal-to-noise when measuring bacteria using IFC.…”
Section: Introductionmentioning
confidence: 99%